Political Vlogs on YouTube and their Role in the Promotion of Hate Speech - Nadeem, Rana Umair (Annals of Human and Social Sciences, 2023)
Digital media became a significant tool for political communication and citizen journalists became more active on YouTube, Facebook, and Twitter, and these platforms emerged as a major source of political information. These citizen journalists are disseminating the news and their analysis in the form of Vlogs on YouTube. The purpose of this study is to study the perception of YouTube viewers about hate speech in political Vlogs uploaded by Pakistani YouTubers and the mediating role of political discourse. A quantitative method of survey Interviews is used to analyze the randomly selected (N = 400) YouTube viewers. This study investigated the Political Discourse positively mediating the correlation between watching political Vlogs on YouTube and Hate speech in viewers. According to their attitude, political beliefs, and exposure, citizen journalists actively promote political speeches and messages through YouTube videos.